Pilonidal sinus disease of the penis: A case report and review of the literature. (25th October 2020) - Shanmugathas, Nimlan; Yassin, Musaab; Ross, Christopher; Minhas, Suks
Abstract: Pilonidal sinus disease (PSD) is an acquired pathological condition more commonly seen in the natal cleft of the sacrococcygeal area, although its presentation is not limited to the natal cleft and it can present in other regions of the body such as the breast, umbilicus, scalp and penis. We present the case of a 28‐year‐old gentleman who presented to his local Urology outpatient clinic with an unusual penile lesion that was later identified as a pilonidal sinus. This was treated with radical circumcision and penile reconstruction with a good functional outcome. For surgeons unaccustomed to PSD presenting on the penis, there is a potential for delay in diagnosis and sub‐optimal management of this rare lesion.